Effect of Work Stress, Workload, and Job Satisfaction on Employees' Turnover Intention Perceptions at PT Cemerlang Lestari in Balikpapan - Hermin Nainggolan; Agung Gunawan (Enrichment : Journal of Management, 2021)
This study aims to determine the effect of work stress, workload and job satisfaction on employee turnover intention at PT Cemerlang Lestari in Balikpapa, either partially or simultaneously. The sample of this research is 75 employees of PT Cemerlang Lestari in Balikpapan who are still actively working selected using random sampling technique. The method used is quantitative method, data collection is carried out using primary data through direct questionnaires to respondents. Data were analyzed by validity and reliability tests, as well as multiple linear regression analysis t test, f test, using the SPSS 24.0 program. The results showed that work stress (X1) had a positive and significant effect on employee turnover intention (Y), workload (X2) had a positive and significant effect on employee turnover intention (Y) and job satisfaction (X3) had no negative effect on employee turnover intention. (Y). The results of this study also support previous research from Bina Hardi, et al. (2018) which states that work stress (X1) and workload have a positive effect on turnover intention (Y), and rejects the results of research by Aharon Tziner et al. (2015) which states that work stress (X1) and job satisfaction (X3) have a negative or no effect on turnover intention.